Institutional and organizational support for financial investigations of economic crime in international practice - Karapetyan, Olha; Skakun, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article analyzes the institutional and organizational support of financial investigations of economic crime in developed countries. The institutional models of counteracting economic crime that are characteristic of individual countries are considered. The reference models of countries in which existing and effective mechanisms of combating economic crime exist. The article substantiates a number of provisions of the international practice of financial investigations of economic crime, which can be implemented to domestic realities